2013
DOI: 10.1128/jvi.03130-12
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Subunit Beta Interacts with the Capsid Protein and Antagonizes the Growth of Classical Swine Fever Virus

Abstract: The capsid (C) protein of the Flaviviridae family members is involved in nucleocapsid formation and virion assembly. However, the influence of C protein-interacting partners on the outcome of pestivirus infections is poorly defined. In this study, hemoglobin subunit beta (HB) was identified as a C protein-binding protein by glutathione S-transferase pulldown and subsequent mass spectrometry analysis of PK-15 cells, which are permissive cells for classical swine fever virus (CSFV). Coimmunoprecipitation and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…However, the cross-linking function between the Raf/MEK1/2/ERK1/2 and JAK-STAT pathways has not been illustrated in different cell lines. We have previously shown that addition of recombinant IFN-β to CSFV-infected cells dramatically decreases the yields of progeny virus (46). In the present work, we show that the expression of p-STAT1 in PK-15 cells is induced during the early phase of CSFV infection, indicating that CSFV can activate the JAK-STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cross-linking function between the Raf/MEK1/2/ERK1/2 and JAK-STAT pathways has not been illustrated in different cell lines. We have previously shown that addition of recombinant IFN-β to CSFV-infected cells dramatically decreases the yields of progeny virus (46). In the present work, we show that the expression of p-STAT1 in PK-15 cells is induced during the early phase of CSFV infection, indicating that CSFV can activate the JAK-STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Through mechanisms mediated by interaction between virus and host proteins, the virus could modulate the host cell response, permitting the virus to manipulate host metabolic pathways to facilitate its replication. In that regard, we have already reported that structural CSFV Core protein interacts with host SUMO1, IQGAP1, UBC9 and OS9 [11][12][13][14]; the interaction of nonstructural protein p7, a viroporin, with CAMLG [28]; recently, we characterized the interaction of major structural glycoprotein E2 with host proteins PPP1CB and DCNT6 [20,21]. Interestingly, some of these host-virus protein-protein interactions also play a role determining virus virulence in swine [11][12][13]21].…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the identification of host cell proteins specifically interacting with these virus proteins during infection is a relatively new field of CSFV research. CSFV Core protein has been shown to interact with IQ motif-containing GTPase activating protein 1 (IQGAP1), ubiquitin-conjugating enzyme 9 (UBC9), small ubiquitin-related modifier 1 (SUMO1), and hemoglobin subunit beta (HB) [11][12][13][14]. E rns has been demonstrated to interact with the Laminin receptor [15].…”
Section: Introductionmentioning
confidence: 99%
“…CSFV has developed different strategies to subvert the innate immune system to facilitate its replication in the host cell. These include the proteasomal degradation of IRF3 mediated by N pro (Ruggli et al, 2003;La Rocca et al, 2005), RNase activity of E rns (Bauhofer et al, 2005;Matzener et al, 2009), and the antagonism of the hemoglobin b-subunit (HB)-induced interferon production by the CSFV C protein (Li et al, 2013b), etc. This may explain why vSM-IRF3 and EGFP-CSFV did not induce the IFN-b production.…”
Section: Discussionmentioning
confidence: 99%